Fucoidan's conventional and hydrothermal alginate extraction biorefinery: Effect of the extraction of alkaline treatment towards alginate's intrinsic viscosity of brown algae ofÂ Sargassum cristaefolium - Sugiono, Sugiono; Ferdiansyah, Doni (Food Science and Technology Journal (Foodscitech), 2019)
Brown algae can be functioned as the feedstock on the alginate and fucoidan's sequential extraction biorefinery process. This research aims to obtain the condition of the alkaline treatment process, which provides maximum response towards intrinsic viscosity ofÂ Sargassum cristaefoliumÂ alginate on the integrated alginate and fucoidan extraction biorefinery process. Factorial Experiment Design of 2k is used to understand the effect of temperature, time, and the concentration of Na2CO3 towards the response of alginate's intrinsic viscosity and determine the correct equation model on the first order of experiment. The research indicated that the different parameters of temperature, time, and Na2CO3 extraction process are tangibly influenced the increasing response of the alginate's intrinsic viscosity, which later reduced after reached its maximum point. The highest alginate intrinsic viscosity of 397.32 ml/g happened during the parameters of the temperature of 60oC, time of 120 minutes, and Na2CO3 concentration of 3%. Therefore, the extraction central point design of 60oC temperature, 120 minutes of duration, and 3% concentration of Na2CO3 is considered correct, and the first-order polynomial experiment model is shaped in the quadratic form.